2012
DOI: 10.1002/jat.2782
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage kinetics and apoptosis in ivermectin‐treated chinese hamster ovary cells

Abstract: A comet assay was used to analyze DNA damage kinetics in Chinese hamster ovary (CHO-K1) cells induced by antiparasitic ivermectin (IVM) and the IVM-containing technical formulation Ivomec® (IVO; 1% IVM). Cells were treated with 50 µg ml(-1) IVM and IVO for 80 min, washed and re-incubated in antiparasiticide-free medium for 0-24 h until assayed using the single-cell gel electrophoresis assay (SCGE). Cell viability remained unchanged up to 3 h of incubation. After 6 h of treatment, cell survival decreased up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…Unfortunately, the identity of the components present within the excipient formulations was not made available by the manufacturer. These final remarks are in accord with previous observations not only reported by us but also by other research groups indicating the presence of xenobiotics within the composition of the commercial formulations with genotoxic and cytotoxic effects as previously mentioned [44,46,51,[66][67][68]89,90,[125][126][127][128][129][130]. Hence, risk assessment must also consider additional genocytotoxic effects caused by the excipient/s.…”
Section: Final Remarkssupporting
confidence: 91%
See 1 more Smart Citation
“…Unfortunately, the identity of the components present within the excipient formulations was not made available by the manufacturer. These final remarks are in accord with previous observations not only reported by us but also by other research groups indicating the presence of xenobiotics within the composition of the commercial formulations with genotoxic and cytotoxic effects as previously mentioned [44,46,51,[66][67][68]89,90,[125][126][127][128][129][130]. Hence, risk assessment must also consider additional genocytotoxic effects caused by the excipient/s.…”
Section: Final Remarkssupporting
confidence: 91%
“…Although pesticides are developed through very strict regulation processes to function with reasonable certainty and minimal impact on human health and the environment, serious concerns have been raised about health risks resulting from occupational exposure and from residues in food and drinking water [41]. Several investigations have demonstrated that the additive compounds present in pesticide commercial formulations have the ability to induce cellular toxicity, including genotoxicity and genotoxicity by themselves, separate from the active ingredient [42][43][44][45][46][47][48][49][50][51]. Accordingly, risk assessment must also consider additional toxic effects caused by the excipient(s).…”
Section: Problem Frameworkmentioning
confidence: 99%
“…Although pesticides are developed through very strict regulation processes to function with reasonable certainty and minimal impact on human health and the environment, serious concerns have been raised about health risks resulting from occupational exposure and from residues in food and drinking water (WHO, 1990). Several investigations have demonstrated that the additive compounds present in pesticide commercial formulations have the ability to induce toxicity and cellular damage by themselves, separate from the active ingredient (Belden et al, 2010;Brühl et al, 2013;Lin and Garry, 2000;Mann and Bidwell, 1999;Molinari et al, 2013;Nikoloff et al, in press, 2012;Rayburn et al, 2005;Soloneski and Larramendy, 2010;Zeljezic et al, 2006). Hence, risk assessment must also consider additional toxic effects caused by the excipient(s).…”
Section: Discussionmentioning
confidence: 99%
“…Abamectin induced single-strand DNA breaks in the rat hepatocytes (EPA 1989); there are rare studies on the genotoxicity of abamectin. Molinari et al (2009Molinari et al ( , 2013 found that ivermectin did not induce SCE in the CHO K1 cells; however, it induced single-DNA-strand breaks. Ivermectin showed genotoxic effects on the somatic cells of the mother Wister rats and higher MN frequencies in the red blood cells from the embryos' umbilical cord compared with the control (El-Ashmawy et al 2011).…”
Section: Avermectin Exerted In Vivo and In Vitro Cytotoxic Actions Inmentioning
confidence: 97%